Integration of proxy intermediate omics traits into a nonlinear two-step model for accurate phenotypic prediction - Hayato Yoshioka; Tristan Mary-Huard; Julie Aubert; Yusuke Toda; Yoshihiro Ohmori; Yuji Yamasaki; Hisashi Tsujimoto; Hirokazu Takahashi; Mikio Nakazono; Hideki Takanashi; Toru Fujiwara; Mai Tsuda; et al. (Theoretical and Applied Genetics, 2026)

Virus induced gene silencing in Antirrhinum majus using the Cucumber mosaic virus vector: Functional analysis of the AINTEGUMENTA (Am-ANT) gene of A. majus - Bo Min Kim; Jun-ichi Inaba; Chikara Masuta (Horticulture, Environment, and Biotechnology, 2011)

Amphibian chytridiomycosis in Japan: distribution, haplotypes and possible route of entry into Japan - KOICHI GOKA; JUN YOKOYAMA; YUMI UNE; TOSHIRO KUROKI; KAZUTAKA SUZUKI; MIRI NAKAHARA; AREI KOBAYASHI; SHIGEKI INABA; TOMOO MIZUTANI; ALEX D. HYATT (Molecular Ecology, 2009)
A serious disease of amphibians caused by the chytrid fungus Batrachochytrium dendrobatidis was first found in Japan in December 2006 in imported pet frogs. This was the first report of chytridiomycosis in Asia. To assess the risk of pandemic chytridiomycosis to Japanese frogs, we surveyed the distribution of the fungus among captive and wild frog populations. We established a nested PCR assay that uses two pairs of PCR primers to amplify the internal transcribed spacer (ITS) region of a ribosomal RNA cassette to detect mild fungal infections from as little as 0.001 pg (1 fg) of B. dendrobatidis DNA. We collected swab samples from 265 amphibians sold at pet shops, 294 bred at institutes and 2103 collected at field sites from northern to southwestern Japan. We detected infections in native and exotic species, both in captivity and in the field. Sequencing of PCR products revealed 26 haplotypes of the B. dendrobatidis ITS region. Phylogenetic analysis showed that three of these haplotypes were specific to the Japanese giant salamander ( Andrias japonicus ) and appeared to have established a commensal relationship with this native amphibian. Many other haplotypes were carried by alien amphibians. The highest genetic diversity of B. dendrobatidis was found in the American bullfrog ( Rana catesbeiana ). Some strains of B. dendrobatidis appeared to be endemic to Japanese native amphibians, but many alien strains are being introduced into Japan via imported amphibians. To improve chytridiomycosis risk management, we must consider the risk of B. dendrobatidis changing hosts as a result of anthropogenic disturbance of the host‐specific distribution of the fungus.

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)